Solomon Islands Statistical Appendix (IMF Staff Country Reports, 2006)
The paper presents statistical data on real sector indicators, real GDP, formal employment, central government operations, revenue and grants, expenditure, budget financing, gross domestic debt, and equity investment in Solomon Islands. It also presents the summary accounts of the banking system, assets and liabilities of the Development Bank of Solomon Islands, commercial bank advances, loans, and interest rates, balance of payments, trade indicators, composition of exports and imports, medium- and long-term external government debt-service payments, external debt indicators, and exchange rate indicators of the country